Nebulized Magnesium Sulphate Versus Saline as an Adjuvant in Acute Exacerbation of Chronic Obstructive Pulmonary Disease in a Tertiary Centre of Nepal: A Randomized Control Study - Bajracharya, Manjita; Acharya, Ramesh P; Neupane, Ram P; Sthapit, Rekha; Tamrakar, Apurva R (Journal of Institute of Medicine Nepal, 2021)
Introduction Magnesium has been shown to have bronchodilator properties in asthma and chronic obstructive pulmonary disease (COPD). Therapeutic benefits of nebulized magnesium in asthma has been seen. The purpose of this study was to compare therapeutic benefits of nebulised magnesium sulphate as an adjuvant with normal saline in patients with COPD exacerbation. Methods It was a randomized single blind interventional study of 172 cases of acute exacerbation of COPD presenting (AECOPD) with a peak expiratory flow rate (PEFR) <300 L/min measured 20 min after initial management. Patients received 5 mg salbutamol mixed with 3 ml isotonic magnesium sulphate or 3 ml normal saline on three occasions at 30 min intervals via nebulizer. The primary outcome measured was PEFR at 90 min and hospital admission, noninvasive or invasive ventilation and mortality were taken as secondary outcomes. Results The mean PEFR were 86.3±11.9 l/min, 97.6±19.1 l/min and 99.6±15.2 l/min after nebulization with magnesium sulphate and 79.17±14.11 l/min, 90.17±18.27 l/min and 93.17±20.63 l/min at 30, 60 and 90 minutes respectively in normal saline group which were statistically significant differences. Total 91.9% were admitted in ward and 8.1% got admitted in Medical and intermediate intensive care units from magnesium group and 81.7% were admitted in ward and 18.3% required ICU admissions in saline group. Differences in ventilation and mortality were insignificant. Conclusion Nebulized magnesium sulphate as an adjuvant to salbutamol treatment in the setting of AECOPD has therapeutic benefit on PEFR but no effect in terms of hospital admission, requirement of invasive or non-invasive ventilation and mortality.